An Activity Theoretical Perspective on Writing and Supervising a Master’s Thesis - Bastola, Madhu Neupane (English Language Teaching Perspectives, 2023)
For students as novice researchers, a master’s thesis is the most demanding component because it requires them to display and learn research skills and work independently. Unfortunately, master thesis supervision has remained far from the limelight of university pedagogy. Drawing on mixed-methods research, this paper characterizes the writing and supervising of a master’s thesis from the perspective of cultural-historical activity theory. It presents various components of the activity system and how the interaction between these systems creates conflicts and contradictions. The implications of such an understanding to effective master’s thesis writing and supervision have been provided.